α2-macroglobulin-rich serum as a master inhibitor of inflammatory factors attenuates cartilage degeneration in a mini pig model of osteoarthritis induced by “idealized” anterior cruciate ligament reconstruction - Zhao, Ruipeng; Wei, Xiaochun; Zhang, Chengming; Wu, Hongru; Xiang, Chuan; Li, Haoqian; Duan, Wangping; Duan, Zhiqing; Li, Chunjiang; Zhao, Yu; Huang, Lingan (Frontiers in Pharmacology, 2022)
Post-traumatic osteoarthritis is a special type of osteoarthritis and a common disease, with few effective treatments available. α2-Macroglobulin (α2M) is important to chondral protection in post-traumatic osteoarthritis. However, its injection into xenogeneic joint cavities involves safety hazards, limiting clinical applications. Exploring serum α2M-enriching strategies and the therapeutic effect and mechanism of α2M-rich serum (α2MRS) autologous joint injection to treat post-traumatic osteoarthritis has significant value. In the present study, a unique filtration process was used to obtain α2MRS from human and mini pig serum. We evaluated the potential of α2MRS in protecting against post-surgery cartilage degeneration. We identify the potential of α2MRS in reducing the expression of inflammatory cytokines and factors that hasten cartilage degeneration in post-operative conditions leading to post-traumatic osteoarthritis. The potential of α2MRS was analyzed in interleukin-1β induced human chondrocytes and mini pig models. In the chondrocyte model, α2MRS significantly promoted human chondrocyte proliferation and reduced apoptosis and chondrocyte catabolic cytokine gene transcription and secretion. The anterior cruciate ligament autograft reconstruction model of mini pigs was randomized into groups, operated on, and injected with α2MRS or saline. The results showed that α2MRS injection significantly suppressed the levels of inflammatory factors, improved gait, and showed significantly lower cartilage degeneration than the groups that did not receive α2MRS injections. This study highlights the chondroprotective effects of α2MRS, elucidated its potential applications against cartilage degeneration, and may provide a basis for the clinical translation of α2MRS.